Norepinephrine Is a Major Regulator of Pineal Gland Secretory Activity in the Domestic Goose (Anser anser) - Ziółkowska, Natalia; Lewczuk, Bogdan (Frontiers in Physiology, 2021)
This study determined the effect of norepinephrine and light exposure on melatonin secretion in goose pineal explants. Additionally, it investigated changes in the content of norepinephrine, dopamine, and their metabolites [3,4-dihydroxyphenylacetic acid; vanillylmandelic acid (VMA); homovanillic acid] in goose pineal glands in vivo under 12 h of light and 12 h of darkness (LD), a reversed cycle (DL), constant light (LL), and constant darkness (DD). In vitro content of melatonin was measured by radioimmunoassay; contents of catecholamines and their metabolites were measured by high-performance liquid chromatography. Exposure of pineal explants to LD or DL established rhythmic melatonin secretion; this rhythm was much better entrained with norepinephrine exposure during photophase than without it. When the explants were kept in LL or DD, the rhythm was abolished, unless NE was administered during natural scotophase of a daily cycle. In vivo, norepinephrine and dopamine levels did not display rhythmic changes, but their respective metabolites, HMV and VMA, displayed well-entrained diurnal rhythms. These results indicate that norepinephrine and sympathetic innervation play key roles in regulation of pineal secretory activity in geese, and that pineal levels of VMA and HMV provide precise information about the activity of sympathetic nerve fibers in goose pineal glands.